ANALISIS TIPE FLUIDA MANIFESTASI PANAS BUMI DI DESA KALEOSAN KABUPATEN MINAHASA UTARA - Windy Wantalangi; Rolles Nixon Palilingan; Jeferson Polii (Charm Sains: Jurnal Pendidikan Fisika, 2020)
Geothermal field exploration and development activities are carried out in an effort to find geothermal resources, prove the existence of the resources and produce and utilize their fluids. Geothermal is a natural resource in the form of hot water or steam that forms in the earth's reservoirs through subsurface water heating by hot rocks. This study aims to determine the type of fluid and reservoir in Kaleosan Village, North Minahasa Regency. Areas that have geothermal potential are marked by the discovery of several geothermal manifestations in the form of hot springs. By using the ternary diagram plot method in the Kaleosan Village area of North Minahasa Regency, it was found that the reservoir in the area was a water-dominated type with an HCO3 content of 204 mg / L, Cl of 479 mg / L, and SO4 of 69 mg / L or based on the percentage of each parameter. has values ranging from HCO3 27%, Cl 64%, and SO4 9% which indicates that chloride(Cl) is the dominant content in the geothermal field.